Preparation method and application of cellulose-based film with ultraviolet shielding function

By grafting the oxidized nanocellulose with folic acid graft modification, a cellulose-based film with ultraviolet shielding ability was prepared, which solved the problem of the cellulose-based film lacking ultraviolet shielding, and achieved the effect of high transparency and strong ultraviolet shielding.

CN119686148APending Publication Date: 2025-03-25INNER MONGOLIA JUMING ENVIRONMENTAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411886566.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing cellulose-based film lacks ultraviolet shielding capabilities, which hinders its further development and utilization in the packaging field.

Method used

By grafting the oxidized nanocellulose and folic acid, a cellulose-based film with ultraviolet shielding ability is formed. The method includes adding folic acid solution to the oxidized nanocellulose suspension and filtration under vacuum to form a dense film.

Benefits of technology

It realizes that the ultraviolet light transmission is maintained in the visible light area (600nm) while shielding ultraviolet rays in the entire band while maintaining a high light transmittance of more than 90%, achieving the effect of high transparency and strong ultraviolet ray shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119686148A_ABST
    Figure CN119686148A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a cellulose-based film with an ultraviolet shielding function. The method comprises the steps of preparation of cellulose, preparation of oxidized nanocellulose and preparation of the cellulose-based film with the ultraviolet shielding function. The invention also provides an application for preparing a material which has permeability to visible light and can shield total ultraviolet rays. The cellulose-based thin film can shield ultraviolet rays in a full wave band, meanwhile, the light transmittance of the cellulose-based thin film in a visible light region exceeds 90%, and high-transparency and strong ultraviolet ray shielding in the true sense is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cellulose-based films, and in particular relates to a preparation method and application of a cellulose-based film with ultraviolet shielding function. Background Art

[0002] Ultraviolet rays are usually divided into UVC (200-280nm), UVB (280-315nm), and UVA (315-400nm) according to their wavelength. Among them, although UVC, as a short-wave ultraviolet ray, has high energy, most of it will be absorbed by the ozone layer and cannot reach the ground. In addition, for some ultraviolet light-sensitive products (such as photosensitive organic matter, food, medicine, etc.), strong ultraviolet radiation may cause changes in their properties, thereby causing irreversible damage. Therefore, ultraviolet protection becomes crucial. At the same time, methods for developing renewable, biodegradable and multifunctional materials have become a research hotspot. In particular, the development of a new generation of biomass film materials requires that these film materials not pollute the environment while exhibiting excellent performance. Cellulose is a natural polymer with excellent film-forming properties, biocompatibility, non-toxicity, degradability and good mechanical properties. It has been used to prepare various functional composite film materials and has been widely used in the packaging field to replace petroleum-based plastic products.

[0003] Films made from cellulose nanofibers have the advantages of high transparency, good mechanical properties and degradability, but they do not have UV shielding ability, which hinders their further development and utilization. Studies have shown that the introduction of UV shielding agents into nanocellulose can construct UV shielding materials. Commonly used UV shielding agents include organic small molecules (benzophenone, benzotriazole and avobenzone derivatives, etc.), inorganic metal oxides (TiO2, CeO2, SiO2, ZnO and Al2O3, etc.) and graphene oxide (GO). However, organic UV absorbers have problems such as photodegradation, migration and aggregation; while inorganic metal oxides have problems such as poor photostability, poor biocompatibility and easy aggregation of particles. On the other hand, inorganic nanoparticles always show obvious photocatalytic effects and can degrade polymer matrices, which greatly limits their application in UV shielding film materials. In order to solve the above problems and use green organic molecules that absorb UV rays more safely, recent research has focused on biomass materials such as lignin. Biomass films are prepared by mixing UV-resistant lignin with various nanofibers. Although the films have good UV shielding effects, their fatal drawback is that the transparency of the films is not high, which affects the visible light transmittance of the films. Therefore, it is necessary to develop highly transparent, fully UV-shielding and economical UV-blocking films. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a cellulose-based film with ultraviolet shielding function and its application in view of the deficiencies of the above-mentioned prior art. The cellulose-based film can shield ultraviolet rays in the entire band, and at the same time, the transmittance in the visible light region (600nm) exceeds 90%, achieving truly high transparency and strong ultraviolet shielding.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a cellulose-based film with ultraviolet shielding function, the method comprising:

[0006] S1. Preparation of cellulose: NaOH and Na2SO3 were dissolved in deionized water, followed by adding kraft paper powder, and heated at 100°C for 6 hours. The residue was then washed with deionized water until neutral. The washed residue was then completely immersed in a 3 mol / L H2O2 solution, and continued to be heated at 100°C for 3 hours. The resultant was washed with deionized water until neutral, and dried to obtain cellulose.

[0007] S2. Preparation of oxidized nanocellulose: NaBr, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical and the cellulose obtained in S1 were dissolved in a Na2CO3 / NaHCO3 buffer solution, and then NaClO was added dropwise to the system, and then the pH value was adjusted to 10.4-10.8 with a 0.5 mol / L NaOH solution, and then reacted in a water bath at a temperature of 30°C for 4 hours, and finally the reaction was terminated with 5 mL of anhydrous ethanol, and the product after the reaction was washed with deionized water to neutrality, and then the product washed to neutrality was dissolved in deionized water, and ultrasonicated with a cell ultrasonic pulverizer to obtain an oxidized nanocellulose suspension;

[0008] S3. Preparation of cellulose-based film with UV shielding function:

[0009] 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide were added to the oxidized nanocellulose suspension obtained in S2 for activation for 30 minutes, and then folic acid solution was added and stirred for reaction for 24 hours. After the reaction was completed, it was poured into a sand core funnel equipped with a filter membrane, and vacuum filtered for 10 hours at a pressure of -0.09 MPa to obtain a dense film. The obtained film was removed from the filter membrane, and the film was wrapped with two layers of filter paper and sandwiched between glass plates. After drying at room temperature, a cellulose-based film with ultraviolet shielding function was obtained.

[0010] In the present invention, folic acid is used to graft and modify oxidized nanocellulose, and an amide bond is formed by reaction between the carboxyl group of the oxidized nanocellulose and the amino group of the folic acid. After the modification, the oxidized nanocellulose that does not have UV resistance acquires the ability to resist UV rays.

[0011] The folic acid-modified oxidized nanocellulose suspension is subjected to vacuum filtration to form a membrane.

[0012] Preferably, the usage ratio of NaOH, Na2SO3, deionized water and leather paper powder in S1 is 20g:10g:200mL:5g.

[0013] Preferably, the molar ratio of Na2CO3 to NaHCO3 in the Na2CO3 / NaHCO3 buffer solution in S2 is 7:3.

[0014] Preferably, the amount ratio of NaBr, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, cellulose and NaClO described in S2 is 0.5g:0.05g:2.5g:25mL.

[0015] Preferably, the folic acid solution in S3 is prepared by dissolving 50 mg of folic acid in 10 mL of dimethyl sulfoxide and subjecting the solution to ultrasonic treatment for 10 min.

[0016] Preferably, the filter membrane in S3 is a mixed cellulose ester membrane with a pore size of 0.2 μm.

[0017] Preferably, the dosage ratio of the oxidized nanocellulose suspension, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and dimethyl sulfoxide solution of folic acid in S3 is 20 mL: 40 mg: 30 mg: (1 to 4) mL.

[0018] Preferably, the average thickness of the cellulose-based film with ultraviolet shielding function in S3 is 50 μm.

[0019] Preferably, the cellulose-based film with ultraviolet shielding function in S3 has a light transmittance of 0% in the ultraviolet region and a visible light transmittance of 90.61% to 93.12% at 600 nm.

[0020] The present invention also provides the use of a cellulose-based film with ultraviolet shielding function prepared by the above preparation method, wherein the cellulose-based film is used to prepare a material that is transparent to visible light and shields all ultraviolet rays.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The cellulose-based film with ultraviolet shielding function prepared by the present invention solves the problem that a simple cellulose-based film has no ultraviolet shielding ability. The raw material source of the present invention is wide, and it is pollution-free to the environment. It can shield ultraviolet rays in the entire band, and at the same time, the transmittance in the visible light region (600nm) exceeds 90%, achieving high transparency and strong ultraviolet shielding in a true sense.

[0023] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a graph showing the detection results of the UV-visible spectrophotometer of Examples 1-4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0025] Reagent materials in the following examples: kraft paper was provided by a local paper mill in Hohhot; sodium sulfite (Na2SO3) was purchased from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd.; sodium hydroxide (NaOH) was purchased from Tianjin Zhiyuan Chemical Reagent Co., Ltd.; hydrogen peroxide (H2O2) was purchased from Sinopharm Chemical Reagent Co., Ltd.; sodium hypochlorite (NaClO), sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), and dimethyl sulfoxide (DMSO) were purchased from Tianjin Fuchen Chemical Reagent Co., Ltd.; sodium bromide (NaBr) was purchased from Tianjin Shengao Chemical Reagent Co., Ltd.; 2,2,6,6-tetramethylpiperidin-1-oxyl free radical (TEMPO) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; folic acid, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), and N-hydroxysuccinimide (NHS) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; the filter membrane was a commercial mixed cellulose ester membrane with a pore size of 0.2 μm, purchased from Tianjin Jinteng Experimental Equipment Co., Ltd.; all reagents were used without purification, and deionized water (resistivity ≥18.25 MΩcm) was used in all experiments.

[0026] Example 1

[0027] The preparation method of the cellulose-based film with ultraviolet shielding function of this embodiment is as follows:

[0028] S1. Preparation of cellulose: 20 g of NaOH and 10 g of Na2SO3 were mixed in 200 mL of deionized water, followed by the addition of 5 g of kraft paper powder, and the mixture was heated at 100°C for 6 h. The residue was washed with deionized water until it was neutral, and then the washed residue was completely immersed in a 3 mol / L H2O2 solution, and the mixture was further heated at 100°C for 3 h. The resultant was washed with deionized water until it was neutral, and then dried to obtain cellulose;

[0029] S2. Preparation of oxidized nanocellulose: 0.5 g NaBr, 0.05 g 2,2,6,6-tetramethylpiperidin-1-oxyl free radical and 2.5 g cellulose obtained in S1 were dissolved in 350 mL Na2CO3 / NaHCO3 buffer solution, and then 25 mL NaClO was added dropwise to the system, and then the pH value was adjusted to 10.4 with a 0.5 mol / L NaOH solution, and then reacted in a water bath at a temperature of 30°C for 4 h, and finally the reaction was terminated with 5 mL of anhydrous ethanol, and the product after the reaction was washed with deionized water to neutrality, and then the washed product to neutrality was dissolved in deionized water, and ultrasonicated with a cell ultrasonic pulverizer to obtain an oxidized nanocellulose suspension;

[0030] The molar ratio of Na2CO3, NaHCO3 and ionized water in the Na2CO3 / NaHCO3 buffer solution is 7:3;

[0031] S3. Preparation of cellulose-based film with UV shielding function:

[0032] To the oxidized nanocellulose suspension obtained in 20 mL of S2, 40 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 30 mg of N-hydroxysuccinimide were added for activation for 30 minutes, and then 1 mL of folic acid solution was added and stirred for reaction for 24 hours. After the reaction was completed, it was poured into a sand core funnel equipped with a filter membrane, and vacuum filtered for 10 hours at a pressure of -0.09 MPa to obtain a dense film. The obtained film was removed from the filter membrane, wrapped with two layers of filter paper and sandwiched between glass plates, and dried at room temperature to obtain a cellulose-based film with an average thickness of 50 μm and a UV shielding function; the filter membrane was a mixed cellulose ester membrane with a pore size of 0.2 μm; the preparation method of the folic acid solution was: 50 mg of folic acid was dissolved in 10 mL of dimethyl sulfoxide and ultrasonically treated for 10 minutes.

[0033] The thickness of the cellulose-based film with ultraviolet shielding function in this embodiment is 50 μm±5 μm, and there is a certain deviation of ±5 μm based on the average value of 50 μm.

[0034] At room temperature, the film prepared in this embodiment was tested using a UV-visible spectrophotometer. The test results are as follows: Figure 1 As shown, the film has good transmittance to visible light, the light transmittance in the ultraviolet region (200-315nm) is 0%, and the ultraviolet shielding rate is 96.77%.

[0035] Example 2

[0036] The preparation method of the cellulose-based film with ultraviolet shielding function of this embodiment is as follows:

[0037] S1. Preparation of cellulose: 20 g of NaOH and 10 g of Na2SO3 were mixed in 200 mL of deionized water, followed by the addition of 5 g of kraft paper powder, and the mixture was heated at 100°C for 6 h. The residue was washed with deionized water until it was neutral, and then the washed residue was completely immersed in a 3 mol / L H2O2 solution, and the mixture was further heated at 100°C for 3 h. The resultant was washed with deionized water until it was neutral, and then dried to obtain cellulose;

[0038] S2. Preparation of oxidized nanocellulose: 0.5 g NaBr, 0.05 g 2,2,6,6-tetramethylpiperidin-1-oxyl free radical and 2.5 g cellulose obtained in S1 were dissolved in 350 mL Na2CO3 / NaHCO3 buffer solution, and then 25 mL NaClO was added dropwise to the system, and then the pH value was adjusted to 10.8 with a 0.5 mol / L NaOH solution, and then reacted in a water bath at a temperature of 30°C for 4 h, and finally the reaction was terminated with 5 mL of anhydrous ethanol, and the product after the reaction was washed with deionized water to neutrality, and then the washed product to neutrality was dissolved in deionized water, and ultrasonicated with a cell ultrasonic pulverizer to obtain an oxidized nanocellulose suspension;

[0039] The molar ratio of Na2CO3, NaHCO3 and ionized water in the Na2CO3 / NaHCO3 buffer solution is 7:3;

[0040] S3. Preparation of cellulose-based film with UV shielding function:

[0041] To the oxidized nanocellulose suspension obtained in 20 mL of S2, 40 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 30 mg of N-hydroxysuccinimide were added for activation for 30 minutes, and then 2 mL of folic acid solution was added and stirred for reaction for 24 hours. After the reaction was completed, it was poured into a sand core funnel equipped with a filter membrane, and vacuum filtered for 10 hours at a pressure of -0.09 MPa to obtain a dense film. The obtained film was removed from the filter membrane, wrapped with two layers of filter paper and sandwiched between glass plates, and dried at room temperature to obtain a cellulose-based film with an average thickness of 50 μm and a UV shielding function; the filter membrane was a mixed cellulose ester membrane with a pore size of 0.2 μm; the preparation method of the folic acid solution was: 50 mg of folic acid was dissolved in 10 mL of dimethyl sulfoxide and ultrasonically treated for 10 minutes.

[0042] The thickness of the cellulose-based film with ultraviolet shielding function in this embodiment is 50 μm±5 μm, and there is a certain deviation of ±5 μm based on the average value of 50 μm.

[0043] At room temperature, the film prepared in this embodiment was tested using a UV-visible spectrophotometer. The test results are as follows: Figure 1 As shown, the film has good transmittance to visible light, the light transmittance in the ultraviolet region (200-385nm) is 0%, and the ultraviolet shielding rate is 99.56%.

[0044] Example 3

[0045] The preparation method of the cellulose-based film with ultraviolet shielding function of this embodiment is as follows:

[0046] S1. Preparation of cellulose: 20 g of NaOH and 10 g of Na2SO3 were mixed in 200 mL of deionized water, followed by the addition of 5 g of kraft paper powder, and the mixture was heated at 100°C for 6 h. The residue was washed with deionized water until it was neutral, and then the washed residue was completely immersed in a 3 mol / L H2O2 solution, and the mixture was further heated at 100°C for 3 h. The resultant was washed with deionized water until it was neutral, and then dried to obtain cellulose;

[0047] S2. Preparation of oxidized nanocellulose: 0.5 g NaBr, 0.05 g 2,2,6,6-tetramethylpiperidin-1-oxyl radical and 2.5 g cellulose obtained in S1 were dissolved in 350 mL Na2CO3 / NaHCO3 buffer solution, and then 25 mL NaClO was added dropwise to the system, and then the pH value was adjusted to 10.6 with a 0.5 mol / L NaOH solution, and then reacted in a water bath at a temperature of 30°C for 4 h, and finally the reaction was terminated with 5 mL of anhydrous ethanol, and the product after the reaction was washed with deionized water to neutrality, and then the washed product to neutrality was dissolved in deionized water, and ultrasonicated with a cell ultrasonic pulverizer to obtain an oxidized nanocellulose suspension;

[0048] The molar ratio of Na2CO3, NaHCO3 and ionized water in the Na2CO3 / NaHCO3 buffer solution is 7:3;

[0049] S3. Preparation of cellulose-based film with UV shielding function:

[0050] To the oxidized nanocellulose suspension obtained in 20 mL of S2, 40 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 30 mg of N-hydroxysuccinimide were added for activation for 30 minutes, and then 3 mL of folic acid solution was added and stirred for reaction for 24 hours. After the reaction was completed, it was poured into a sand core funnel equipped with a filter membrane, and vacuum filtered for 10 hours at a pressure of -0.09 MPa to obtain a dense film. The obtained film was removed from the filter membrane, wrapped with two layers of filter paper and sandwiched between glass plates, and dried at room temperature to obtain a cellulose-based film with an average thickness of 50 μm and a UV shielding function; the filter membrane was a mixed cellulose ester membrane with a pore size of 0.2 μm; the preparation method of the folic acid solution was: 50 mg of folic acid was dissolved in 10 mL of dimethyl sulfoxide and ultrasonically treated for 10 minutes.

[0051] The thickness of the cellulose-based film with ultraviolet shielding function in this embodiment is 50 μm±5 μm, and there is a certain deviation of ±5 μm based on the average value of 50 μm.

[0052] At room temperature, the film prepared in this embodiment was tested using a UV-visible spectrophotometer. The test results are as follows: Figure 1 As shown, the film has good transmittance to visible light, the light transmittance in the ultraviolet region (200-395nm) is 0%, and the ultraviolet shielding rate is 99.87%.

[0053] Example 4

[0054] The preparation method of the cellulose-based film with ultraviolet shielding function of this embodiment is as follows:

[0055] S1. Preparation of cellulose: 20 g of NaOH and 10 g of Na2SO3 were mixed in 200 mL of deionized water, followed by the addition of 5 g of kraft paper powder, and the mixture was heated at 100°C for 6 h. The residue was washed with deionized water until it was neutral, and then the washed residue was completely immersed in a 3 mol / L H2O2 solution, and the mixture was further heated at 100°C for 3 h. The resultant was washed with deionized water until it was neutral, and then dried to obtain cellulose;

[0056] S2. Preparation of oxidized nanocellulose: 0.5 g NaBr, 0.05 g 2,2,6,6-tetramethylpiperidin-1-oxyl free radical and 2.5 g cellulose obtained in S1 were dissolved in 350 mL Na2CO3 / NaHCO3 buffer solution, and then 25 mL NaClO was added dropwise to the system, and then the pH value was adjusted to 10.8 with a 0.5 mol / L NaOH solution, and then reacted in a water bath at a temperature of 30°C for 4 h, and finally the reaction was terminated with 5 mL of anhydrous ethanol, and the product after the reaction was washed with deionized water to neutrality, and then the washed product to neutrality was dissolved in deionized water, and ultrasonicated with a cell ultrasonic pulverizer to obtain an oxidized nanocellulose suspension;

[0057] The molar ratio of Na2CO3, NaHCO3 and ionized water in the Na2CO3 / NaHCO3 buffer solution is 7:3;

[0058] S3. Preparation of cellulose-based film with UV shielding function:

[0059] To the oxidized nanocellulose suspension obtained in 20 mL of S2, 40 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 30 mg of N-hydroxysuccinimide were added for activation for 30 min, and then 4 mL of folic acid solution was added for stirring and reaction for 24 h. After the reaction was completed, it was poured into a sand core funnel equipped with a filter membrane, and vacuum filtered for 10 h at a pressure of -0.09 MPa to obtain a dense film. The obtained film was removed from the filter membrane, wrapped with two layers of filter paper and sandwiched between glass plates, and dried at room temperature to obtain a cellulose-based film with an average thickness of 50 μm and a UV shielding function; the filter membrane was a mixed cellulose ester membrane with a pore size of 0.2 μm; the preparation method of the folic acid solution was: 50 mg of folic acid was dissolved in 10 mL of dimethyl sulfoxide and ultrasonically treated for 10 min.

[0060] The thickness of the cellulose-based film with ultraviolet shielding function in this embodiment is 50 μm±5 μm, and there is a certain deviation of ±5 μm based on the average value of 50 μm.

[0061] At room temperature, the film prepared in this embodiment was tested using a UV-visible spectrophotometer. The test results are as follows: Figure 1 As shown, the film has good transmittance to visible light, the light transmittance in the ultraviolet region (200-400nm) is 0%, and the ultraviolet shielding rate is 99.95%.

[0062] Comparative Example 1

[0063] The raw material component of the highly transparent cellulose-based film of this comparative example is 20 mL of oxidized nanocellulose suspension (the same as the oxidized nanocellulose suspension prepared in step S2 of Example 1)

[0064] Pour 20 mL of oxidized nanocellulose suspension into a sand core funnel equipped with a filter membrane and perform vacuum filtration at a pressure of -0.09 MPa for 10 hours to eventually obtain a transparent and dense film. Remove the film from the filter membrane, wrap it with two layers of filter paper and sandwich it between a glass plate and dry it at room temperature to eventually obtain a highly transparent cellulose-based film with an average thickness of 50 μm.

[0065] The thickness of the cellulose-based film with ultraviolet shielding function in this comparative example is 50 μm±5 μm, and there is a certain deviation of ±5 μm based on the average value of 50 μm.

[0066] At room temperature, the film prepared in this embodiment was tested using a UV-visible spectrophotometer. The test results are as follows: Figure 1 As shown, the film has a transmittance of more than 80% for light in the wavelength range of 200-800nm, and does not have the ability to shield ultraviolet rays.

[0067] The cellulose-based film with ultraviolet shielding function prepared by the present invention has excellent ultraviolet shielding performance and high transparency, and the film is tested by an ultraviolet-visible spectrophotometer.

[0068] The cellulose-based film prepared in Comparative Example 1 still has high light transmittance at 200-400nm, and the light transmittance at 600nm is 93.62%, indicating that the cellulose-based film prepared in Comparative Example 1 has no ability to resist ultraviolet rays. The cellulose-based films prepared in Examples 1, 2, 3, and 4 can all resist ultraviolet rays in the ultraviolet region (200-400nm), and the visible light transmittance at 600nm is 93.12%, 92.08%, 91.95%, and 90.61%, respectively, indicating that the cellulose-based film with ultraviolet shielding function prepared in the present invention has high efficiency ultraviolet shielding ability and high transparency.

[0069] The cellulose-based film prepared in Comparative Example 1 can only block 18.47% of UVA and 30.64% of UVB, indicating that the film has basically no effective ultraviolet shielding performance. The UVA shielding efficiency of the cellulose-based films prepared in Examples 1, 2, 3, and 4 are 91.85%, 98.77%, 99.68%, and 99.92%, respectively, and the UVB shielding efficiency is 99.91%, 99.94%, 99.95%, and 99.97%, respectively.

[0070] In summary, the cellulose-based film prepared by the present invention can be used to prepare materials that are transparent to visible light and shield against all ultraviolet rays.

[0071] The cellulose-based film with ultraviolet shielding function prepared by the present invention solves the problem that a simple cellulose-based film has no ultraviolet shielding ability. The raw material source of the present invention is wide, and it is pollution-free to the environment. It can shield ultraviolet rays in the entire band, and at the same time, the transmittance in the visible light region (600nm) exceeds 90%, achieving high transparency and strong ultraviolet shielding in a true sense.

[0072] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a cellulose-based film having ultraviolet shielding function, characterized in that: The method is: S1. Preparation of cellulose: NaOH and Na2SO3 were dissolved in deionized water, and then kraft paper powder was added. After heating at 100°C for 6 hours, the residue was washed with deionized water until neutral. Then, the washed residue was completely immersed in a 3 mol / L H2O2 solution, and continued to heat at 100°C for 3 hours. The resultant was washed with deionized water until neutral, and dried to obtain cellulose. S2. Preparation of oxidized nanocellulose: NaBr, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical and the cellulose obtained in S1 were dissolved in a Na2CO3 / NaHCO3 buffer solution, and then NaClO was added dropwise to the system. The pH value was then adjusted to 10.4-10.8 with a 0.5 mol / L NaOH solution, and the reaction was carried out in a water bath at a temperature of 30°C for 4 hours. Finally, the reaction was terminated with 5 mL of anhydrous ethanol, and the product after the reaction was washed with deionized water to neutrality, and then the product washed to neutrality was dissolved in deionized water, and a cell ultrasonic pulverizer was used to obtain an oxidized nanocellulose suspension; S3. Preparation of cellulose-based film with UV shielding function: 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added to the oxidized nanocellulose suspension obtained in S2 for activation for 30 minutes, and then folic acid solution was added and stirred for reaction for 24 hours. After the reaction was completed, it was poured into a sand core funnel equipped with a filter membrane, and vacuum filtered for 10 hours at a pressure of -0.09 MPa to obtain a dense film. The obtained film was removed from the filter membrane, wrapped with two layers of filter paper and sandwiched between glass plates, and dried at room temperature to obtain a cellulose-based film with ultraviolet shielding function.

2. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The usage ratio of NaOH, Na2SO3, deionized water and kraft paper powder in S1 is 20g:10g:200mL:5g.

3. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The molar ratio of Na2CO3 to NaHCO3 in the Na2CO3 / NaHCO3 buffer solution in S2 is 7:

3.

4. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: As described in S2, the usage ratio of NaBr, 2,2,6,6-tetramethylpiperidin-1-oxyl free radical, cellulose and NaClO is 0.5 g: 0.05 g: 2.5 g: 25 mL.

5. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The folic acid solution described in S3 is prepared by dissolving 50 mg of folic acid in 10 mL of dimethyl sulfoxide and subjecting the solution to ultrasonic treatment for 10 minutes.

6. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The filter membrane in S3 is a mixed cellulose ester membrane with a pore size of 0.2 μm.

7. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The dosage ratio of the oxidized nanocellulose suspension, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and folic acid solution in S3 is 20 mL: 40 mg: 30 mg: (1 to 4) mL.

8. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The average thickness of the cellulose-based film having the ultraviolet shielding function described in S3 is 50 μm.

9. The method for preparing a cellulose-based film with ultraviolet shielding function according to claim 1, characterized in that: The cellulose-based film with ultraviolet shielding function described in S3 has a light transmittance of 0% in the ultraviolet region and a visible light transmittance of 90.61% to 93.12% at 600 nm.

10. An application of a cellulose-based film having ultraviolet shielding function prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The cellulose-based film is used to prepare a material that is transparent to visible light and shields all ultraviolet rays.

Citation Information

Cited By

  • Preparation method of fire-retardant and ultraviolet-resistant bifunctional cellulose film

    CN122749965A